Retrospective matched case-control study evaluating cementless total knee replacements in patients with BMI over 30 kg/m2 or in patients aged 65 yr and younger. Issue 5 (8th September 2021) - Silverstein, Rachel Sanislo; Owashi, Eric Toshio; Rawicki, Nathaniel Levi; Patel, Neel R.; Shatkin, Michael Stephen; Zelicof, Steven B.
Abstract : Background: This study's goal was to compare outcomes in cemented and cementless total knee arthroplasty (TKA) in patients with a body mass index of 30 kg/m 2 or greater or patients aged 65 yr or younger. Methods: A retrospective matched case-control study was performed on 400 consecutive primary TKAs at the same community-based teaching institution by a single fellowship-trained arthroplasty surgeon. One hundred and eighty-six patients met the inclusion criteria for the obese cohort (93 cementless, 93 cemented). One hundred and seventy-one patients met the inclusion criteria of 65 yr of age or younger cohort (85 cementless, 86 cemented). Charts were reviewed for demographics, TKA revisions, Knee Society Score-Knee (KSS-Knee), Knee Society Score-Function (KSS-Function), Knee Injury and Osteoarthritis Outcomes Scores for Joint Replacement outcome scores, and perioperative complications. Results: The average follow-up was 4 years (range 2.5 to 7 yr). Patients demonstrated improved change for minimal clinically important differences values in both the cementless and cemented TKA groups for KSS-Knee and KSS-Function in each cohort. Substantial clinical benefit had improved change for cementless TKAs in both KSS-Knee and KSS-Function scores; however, only the cementless TKA group achieved an improved change in substantial clinical benefit with KSS-Function. Knee Injury and Osteoarthritis Outcomes Scores for Joint Replacement scores were equivalent between both the cementless and cemented cohorts. Conclusions: This study was clinically significant as outcome data remained positive for longer term follow-up in patients with a body mass index of 30 kg/m 2 or greater or those aged 65 yr or younger with cementless total knees. Level of Evidence: Level III.